Exploring the venom of the forest cobra snake: Toxicovenomics and antivenom profiling of Naja melanoleuca - Lauridsen, Line Præst (2017)
A toxicovenomic analysis of the venomof the forest cobra, N. melanoleuca,was performed, revealing the presence of a total of 52 proteins by proteomics analysis. The most abundant proteins belong to the three-finger toxins (3FTx) (57.1 wt%), which includes post-synaptically acting α-neurotoxins. Phospholipases A2 (PLA2) were the second most abundant group of proteins (12.9 wt%), followed by metalloproteinases (SVMPs) (9.7 wt%), cysteine- rich secretory proteins (CRISPs) (7.6wt%), and Kunitz-type serine proteinase inhibitors (3.8 wt%). A number of additional protein families comprised each b3 wt% of venom proteins. A toxicity screening of the fractions, using the mouse lethality test, identified toxicity in RP-HPLC peaks 3, 4, 5 and 8, all of them containing α-neurotoxins of the 3FTx family, whereas the rest of the fractions did not show toxicity at a dose of 0.53 mg/kg. Three polyspecific antivenoms manufactured in South Africa and India were tested for their immunoreactivity against crude venomand fractions of N.melanoleuca. Overall, antivenoms immunorecognized all fractions in the venom, the South African antivenom showing a higher titer against the neurotoxin-containing fractions. This toxicovenomic study identified the 3FTx group of α-neurotoxins in the venom of N. melanoleuca as the relevant targets to be neutralized. Biological significance: A toxicovenomic analysis of the venomof the forest cobra, also known as black cobra, Naja melanoleuca, was performed. Envenomings by this elapid species are characterized by a progressive descending paralysiswhich starts with palpebral ptosis and, in severe cases, ends up with respiratory arrest and death. A total of 52 different proteins were identified in this venom. The most abundant protein family was the three-finger toxin (3FTx) family, which comprises almost 57.1 wt% of the venom, followed by phospholipases A2 (PLA2) (12.9 wt%). In addition, several other protein families were identified in a much lower percentage in the venom. A toxicity screening of the fractions, using the mouse lethality assay, identified four peaks as those having toxicity higher than that of the crude venom. These fractions predominantly contain α-neurotoxins of the 3FTx family. This toxicovenomic characterization agrees with the clinical and experimental manifestations of envenomings by this species, in which a strong neurotoxic effect predominates. Therefore, our findings suggest that immunotherapy against envenomings by N. melanoleuca should be directed towards the neutralization of 3FTxs; this has implications for the improvement of current antivenoms and for the development of novel antivenoms based on biotechnological approaches. A screening of the immunoreactivity of three antivenoms being distributed in sub-Saharan Africa revealed that they immunoreact with the fractions containing α-neurotoxins, although with different antibody titers.